(untitled) (International Journal of Engineering and Computer Science, 2025)
The fast-paced technological development drives periodic evolution of cyber dangers. Every day novel attack techniques appear which display specific features that enable digital system and data breach. The examination in this paper reviews cyber threat historical progression while inspecting modern threat patterns and expected future dangers alongside an analysis about Artificial Intelligence (AI) cyber threat functions and protective mechanisms. Security professionals now use artificial intelligence for defensive and offensive actions throughout their cybersecurity work. AI makes cyber defense improvements but still provide advanced attack technology to hackers which overcomes standard security protocols. AI-driven security threats are predicted to become greater challenges in the future because they may exceed human-operated cyberattacks in size and speed. The self-learning quality of AI systems functions as both an advantage and a problem in cybersecurity operations. This paper examines previous cyber threats together with existing AI-driven security risks and proposed countermeasures that defend against upcoming AI-powered cyber-attacks